Effect of a novel bioceramic root canal sealer on the angiogenesis-enhancing potential of assorted human odontogenic stem cells compared with principal tricalcium silicate-based cements - Keziban Olcay; Pakize Neslihan Taşli; Esra Pamukçu Güven; Gül Merve Yalçın Ülker; Emine Esen Öğüt; Elif Çiftçioğlu; Binnur Kiratli; Fikrettin Şahin (University of São Paulo, 2020)
Abstract Objective: This study evaluated the angiogenesis-enhancing potential of a tricalcium silicate-based mineral trioxide aggregate (ProRoot MTA), Biodentine, and a novel bioceramic root canal sealer (Well-Root ST) in human dental pulp stem cells (hDPSCs), human periodontal ligament stem cells (hPLSCs), and human tooth germ stem cells (hTGSCs). Methodology: Dulbecco's modified Eagle's medium was conditioned for 24 h by exposure to ProRoot MTA, Biodentine, or Well-Root ST specimens (prepared according to the manufacturers' instructions). The cells were cultured in these conditioned media and their viability was assessed with 3-(4,5-dimethyl-thiazol-2-yl)-5-(3-carboxy-methoxy-phenyl)-2-(4-sulfo-phenyl)-2H tetrazolium (MTS) on days 1, 3, 7, 10, and 14. Angiogenic growth factors [platelet-derived growth factor (PDGF), basic ﬁbroblast growth factor (FGF-2), and vascular endothelial growth factor (VEGF)] were assayed by sandwich enzyme-linked immunosorbent assay (ELISA) on days 1, 7, and 14. Human umbilical vein endothelial cell (HUVEC) migration assays were used to evaluate the vascular effects of the tested materials at 6-8 h. Statistical analyses included Kruskal-Wallis, Mann-Whitney U, and Friedman and Wilcoxon signed rank tests. Results: None of tricalcium silicate-based materials were cytotoxic and all induced a similar release of angiogenic growth factors (PDGF, FGF-2, and VEGF) (p>0.05). The best cell viability was observed for hDPSCs (p<0.05) with all tricalcium silicate-based materials at day 14. Tube formation by HUVECs showed a significant increase with all tested materials (p<0.05). Conclusion: The tricalcium silicate-based materials showed potential for angiogenic stimulation of all stem cell types and significantly enhanced tube formation by HUVECs.